Impact of Puberty in Girls on Prevalence of Primary Headache Disorder Among Female Schoolchildren in Kuwait - Alashqar, Abdelrahman; Shuaibi, Sameera; Ahmed, Samar Farouk; AlThufairi, Hawraa; Owayed, Shaikhah; AlHamdan, Fajer; Alroughani, Raed; Al-Hashel, Jasem Yousef (Frontiers in Neurology, 2020)
Background: The prevalence of primary headaches in the pediatric population is remarkably rising and shaped by many factors, of which pubertal status may possibly play a substantial role. Female sex hormones are largely postulated to underlie this potential association by means of structural and physiological phenomena in the brain. Epidemiological studies on primary headaches in the pediatric population in the gulf region remain scarce and further research is crucial. Aims and Objectives: To examine the impact of puberty on the prevalence of primary headache disorders among female school children in Kuwait. Methods: We conducted a cross-sectional study that included Kuwaiti primary and middle school girls from randomly selected schools located in two governorates in Kuwait during the academic year 2018/2019. Prevalence of headache was assessed using the Headache-Attributed Restriction, Disability, Social Handicap and Impaired Participation (HARDSHIP) questionnaire for children and adolescents. Female students answered the question on attainment of menarche with yes or no and whether they attained it before or after experiencing their headaches. Results: The questionnaire was completed by 669 girls with a mean age of 11.44 ± 2.14 years. The lifetime prevalence of any headache was 84.9% as opposed to a 1-year prevalence of primary headache disorders of 47.98% and 1-year prevalence of migraine headache disorder of 23.62%. With respect to diagnostic criteria, migraine headache was the most frequently reported followed by tension type headaches (20.93%), chronic headaches (2.99%), and probable medication-overuse headaches (0.45%.). Post-pubertal females were at significantly higher risk of having primary headaches compared to their pre-pubertal counterparts (64. 26% vs. 34. %; p <0.0001). All types of primary headaches were more significantly prevalent among post-pubertal girls compared to those who are pre-pubertal. Conclusion: Migraine headache is commonly reported among Kuwaiti schoolgirls. Post-pubertal females are at higher risk of developing primary headaches compared to pre-pubertal females. Pubertal transition and female sex hormones may play a significant role in the pathophysiology of headaches, migraines in particular, and further research is therefore needed to investigate the underlying mechanisms.